A qualitative study of risks and protective factors against pregnancy among sexually-active adolescents in Soweto, South Africa. - Edna N Bosire; Katharine Chiseri; Dawn L Comeau; Linda Richter; Aryeh D Stein; Shane A Norris (Public Library of Science (PLoS), 2021)
Risky sexual behaviors contribute to increased risk of adolescent pregnancy. This qualitative study sought to understand risks and protective factors against pregnancy amongst sexually-active adolescents in Soweto, South Africa. We used purposive sampling to recruit women at age 24 years from Soweto, who self-reported having sexual debut by age 15 years. Twenty women were recruited: (i) women who did not become pregnant before 18 years (n = 10) and (ii) women who became pregnant before 18 years (n = 10). In-depth interviews were conducted to understand their family backgrounds, conversations about sex, sexual behaviors, and initiatives taken (or not) during adolescence to prevent pregnancy. Both groups of women reported predisposing risks to early pregnancy including influence from peers to engage in early sex, unstable family relationships and limited conversations about sex. We found that the family is a key institution in supporting adolescents' decisions regarding their behaviors and choices, as are peers and exposures to information. Community Youth Centers, high schools and Youth Friendly Health Services should ensure that adolescents have access to relevant information, including sex education and contraceptives.